The Strengths and Weaknesses of the Joint forest Management in West Bengal - Sarkar, S. K. (Indian Forester, 1994)
In West Bengal the site and situation are different in different parts of the State. The South-West lateritic tract was in severe degradiation. Therefore, priority was given to this area first to form the protection committee, under Joint Forest Management programme and gradually extended to other areas. The strength and weakness of the programme and their remedial measures are suggested.